2001
DOI: 10.1063/1.1383049
|View full text |Cite
|
Sign up to set email alerts
|

Shifting and broadening in the fundamental band of CO highly diluted in He and Ar: A comparison with theory

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 33 publications
6
67
1
Order By: Relevance
“…(26)). More recently Duggan et al (27), Sinclair et al (28), and Luo et al (29) reported precise analysis of CO lineshapes in the (1-0) band broadened by Ar and He at room temperature taking into account narrowing effects. The first attempt to justify experimentally the choice between a soft or hard collision model was done by Henry et al (26) by analyzing an absorption line of CO in a mixture with buffer gases of different masses from He to Xe at low pressures and at room temperature.…”
Section: Introductionmentioning
confidence: 97%
“…(26)). More recently Duggan et al (27), Sinclair et al (28), and Luo et al (29) reported precise analysis of CO lineshapes in the (1-0) band broadened by Ar and He at room temperature taking into account narrowing effects. The first attempt to justify experimentally the choice between a soft or hard collision model was done by Henry et al (26) by analyzing an absorption line of CO in a mixture with buffer gases of different masses from He to Xe at low pressures and at room temperature.…”
Section: Introductionmentioning
confidence: 97%
“…15 It must be stressed that these shifts are not directly observable quantities; for a proper discussion of observable shifts of rovibrational CO lines, see Ref. 33. In conjunction with the contours of Fig.…”
Section: A Computational Detailsmentioning
confidence: 99%
“…However, the comparison of theory and experiment in Ref. 33 is incomplete, since calculation of the symmetric component, and therefore of the total line shift, requires a three-dimensional IPES. Consequently, we compute in this paper the three-dimensional Ar-CO IPES using the CCSD͑T͒ model with a basis set selected from very strict convergence criteria.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, theories that include such refinments were developed for simple molecular systems, and in any case not for non-linear molecules like methane as the absorber. Anyway, it seems that practical calculations are only tractable for linear molecules up to now [90][91][92][93][94]. Further investigations on these points are obviously needed.…”
Section: Collision Dynamicsmentioning
confidence: 99%